Inter-Provincial Migration in Italy: a Comparison Between Italians and Foreigners - Casacchia, Oliviero; Reynaud, Cecilia; Strozza, Salvatore; Tucci, Enrico (European Spatial Research and Policy, 2019)
Internal migration in Italy increased in the 2000s due to foreigners residing in the country. Foreigners have changed the characteristics of Italy’s internal migration. Extended gravity models were run to highlight the differences between the migratory behaviours of Italians and foreigners. The model was implemented to detect the different effects of the Italian and foreign populations, and the distances between the provinces of origin and destinations of the inter-provincial migration of Italians and foreigners. Estimations obtained for the years 1995, 2000, 2005, 2010, and 2015 highlight the different evolutions of the phenomenon.